2004
DOI: 10.1002/cncr.20056
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis in men with prostate carcinoma receiving androgen‐deprivation therapy

Abstract: BACKGROUNDAndrogen‐deprivation therapy (ADT) is prescribed with increasing frequency for men with prostate carcinoma. There is growing concern about the effects of such therapy on the skeleton. In the current review, the authors addressed the current research, diagnostic methods, and treatment recommendations for bone loss and osteoporosis in men with prostate carcinoma who received ADT.METHODSData were obtained from electronic literature searches (for the years 1986 through 2002) and from abstracts and meetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(69 citation statements)
references
References 59 publications
3
64
0
2
Order By: Relevance
“…Areal BMD measured by dual-energy X-ray absorptiometry (DXA) underestimates the degree of cortical BMD loss and microarchitectural deterioration in cortical and trabecular compartments (Hamilton et al 2010). There is a lack of prospective studies reporting fracture rates in men undergoing ADT (Diamond et al 2004). Large retrospective studies report higher fracture rates in these men (Shahinian et al 2005, Shao et al 2013) and fracture post ADT was associated with a 10% 12-month mortality (Shao et al 2013).…”
Section: Bone Lossmentioning
confidence: 99%
See 2 more Smart Citations
“…Areal BMD measured by dual-energy X-ray absorptiometry (DXA) underestimates the degree of cortical BMD loss and microarchitectural deterioration in cortical and trabecular compartments (Hamilton et al 2010). There is a lack of prospective studies reporting fracture rates in men undergoing ADT (Diamond et al 2004). Large retrospective studies report higher fracture rates in these men (Shahinian et al 2005, Shao et al 2013) and fracture post ADT was associated with a 10% 12-month mortality (Shao et al 2013).…”
Section: Bone Lossmentioning
confidence: 99%
“…Subsequent epidemiologic, basic and clinical studies have demonstrated the role of estrogens in PCa to be highly complex (Di Zazzo et al 2016, Rahman et al 2016. The ageassociated rise in PCa incidence coincides with a decrease in circulating free testosterone/E 2 ratio due to declines in hypothalamic-pituitary-testicular axis function and increases in sex hormone binding globulin (SHBG) (Rahman et al 2016, Cooke et al 2017.…”
Section: Effects Of Estradiol On Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21][22] Moreover, about 90% of patients with mCRPC will develop bone metastases, which cause local decreases in bone integrity. Patients are at significant risk of SREs that include pathological fractures, debilitating bone pain requiring palliative radiation therapy and spinal cord compression.…”
Section: Denosumab and Zoledronic Acidmentioning
confidence: 99%
“…20,21 Bone-targeted therapy Bone loss associated with ADT has been shown to increase the risk of fracture. [22][23][24][25][26] Moreover, about 90% of patients with metastatic CRPC will develop bone metastases, which cause local decreases in bone integrity. Patients are at significant risk of SREs that include pathological fractures, debilitating bone pain requiring palliative radiation therapy and spinal cord compression.…”
Section: Palliative Radiationmentioning
confidence: 99%